Feed balances for ruminant livestock: Gridded estimates for data constrained regions - Fraval, Simon; Mutua, John Y.; Amole, Tunde A.; Tolera, Adugna; Feyisa, Tesfaye; Thornton, Philip K.; Notenbaert, An Maria Omer; Adesogan, Adegbola T.; Balehegn, Mulubrhan; Ayantunde, Augustine A.; Zampaligré, Nouhoun; Duncan, Alan J. (Elsevier, 2024)
Demand for animal source foods and livestock feed are forecast to increase across sub-Saharan Africa. In this context, there is a need to estimate the availability of livestock feed to support decision making at local, sub-national and national levels. In this study we assess feed balances for ruminant livestock in Ethiopia and Burkina Faso. Feed availability was estimated using remotely sensed products and detailed feed composition data. Feed requirements were estimated for maintenance, growth, lactation, gestation and locomotion using a data intensive model. Biomass available as animal feed was estimated to be 8.6 tonnes dry matter (DM) per hectare in the Ethiopian highlands and midlands, 3.2 tonnes DM per hectare in the Ethiopian lowlands, 2.9 tonnes DM per hectare in Burkina Faso’s Sudanian agro-ecological zone and 1.0 tonne DM per hectare in the Sahel. The energy requirements of lactating cows were estimated to be 62.1 Megajoules (MJ) per animal per day in the Ethiopian highlands and midlands, 62.7 MJ in the Ethiopian lowlands, 88.5 MJ in Burkina Faso’s Sudanian agro-ecological zone and 53.1 MJ per animal per day in the Sahel. Feed scarcity hotspots are most prominently located in the Ethiopian highlands and the Sahelian agro-ecological zone of Burkina Faso. Demand side policy and investment initiatives can address hotspots by influencing herd sizes, nutritional requirements and herd mobility. Supply side policy and investment initiatives can secure existing feed resources, develop new sources of feed and incentivise trade in feed resources. Improving feed balances will be of value to decision makers with the aims of optimising livestock productivity, minimising exposure to climatic shocks and minimising greenhouse gas emission intensity.